Peer teachers as ultrasound instructors? – a systematic literature review of peer teaching concepts in undergraduate ultrasound education - Lone Winter; Ricarda Neubauer; Johannes Weimer; Christoph F. Dietrich; Agnes Wittek; Lina Schiestl; Milka Marinova; Valentin Sebastian Schäfer; Brigitte Strizek; Florian Recker (BMC Medical Education)
Abstract Background As ultrasound is one of the most utilized imaging procedures in clinical practice in Germany, its integration into undergraduate medical education is imperative. Thereby, the limited availability of qualified instructors is a major challenge. Peer tutors, who are trained to instruct their peers collaboratively, could resolve staff constraints. This systematic review explores the literature on peer teaching in undergraduate ultrasound education, aiming to provide an overview of methodologies, outcomes, and peer teacher training concepts. Methods Following the PRISMA guidelines, a systematic literature review was conducted on the subject of peer teaching in undergraduate ultrasound education. Using PubMed and Google Scholar as databases, studies in English or German involving training concepts for peer teachers in undergraduate ultrasound education, published up to November 21, 2023, were included. Data extraction of original studies followed the PICOS schema with special respect to didactic concepts of peer tutor training programs and the effectiveness of peer teachers compared to faculty instructors. A modified version of the Newcastle–Ottawa Scale (NOS) was used to assess the quality of included studies. Results Finally, the search resulted in 20 relevant original studies, including 16 studies exploring peer teacher training concepts. Predominantly, peer teachers studied in their 4th year of medical school and on average one year further compared to their students. Peer teacher training was integrated into curricula by course-based concepts (93.8%) and internships (50.0%). Didactic modalities varied, encompassing laboratory rotations including the scanning of patients, the scanning of fellow students, lectures, and didactic training. The median training duration was about ten days. Of six comparative studies, five found peer-assisted learning to be comparably effective and one even better than faculty-led courses. Conclusion Despite the growing amount of literature underlining the effectiveness and wide application of peer teaching in ultrasound education, training concepts stay heterogenous without a standardized system for training and qualifying peer teachers. Developing comprehensive guidelines for peer tutor education could increase acceptance and recognition of peer-assisted learning and ensure minimum training standards.